1999
DOI: 10.1016/s0926-9959(98)00140-8
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon-stomach as a cause of chronic iron deficiency anemia in a patient with systemic sclerosis

Abstract: Watermelon-stomach is a rare cause of gastrointestinal bleeding. There has been an increasing number of reports on the association of this lesion with diseases of the scleroderma group, causing chronic, sometimes severe gastrointestinal blood loss. The present report presents the case of a 75-year-old female with limited cutaneous systemic sclerosis and watermelon-stomach, which was the cause of her long-standing sideropenic anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Although there are reported cases when GAVE is the only manifestation of systemic sclerosis [ 29 ], studies have shown that the majority of patients with GAVE, around 60%, have telangiectasias of the skin [ 30 ]. Most of the patients present either with symptomatic iron deficiency anemia (weakness, fatigue, or dyspnea) or asymptomatic anemia (with laboratory findings like low hemoglobin and mean corpuscular volume) [ 19 , 31 ]. The primary physician must suspect GAVE when the anemia is refractory to regular treatment [ 32 ].…”
Section: Clinical Findings and Diagnosismentioning
confidence: 99%
“…Although there are reported cases when GAVE is the only manifestation of systemic sclerosis [ 29 ], studies have shown that the majority of patients with GAVE, around 60%, have telangiectasias of the skin [ 30 ]. Most of the patients present either with symptomatic iron deficiency anemia (weakness, fatigue, or dyspnea) or asymptomatic anemia (with laboratory findings like low hemoglobin and mean corpuscular volume) [ 19 , 31 ]. The primary physician must suspect GAVE when the anemia is refractory to regular treatment [ 32 ].…”
Section: Clinical Findings and Diagnosismentioning
confidence: 99%
“…Dieser endoskopische Befund erinnert an die Oberflächenzeichnung einer Wassermelone, deshalb wurde der Begriff "Wassermelonen-Magen" 1984 von Jabbari et al [3] eingeführt. Betroffene Patienten sind zumeist Frauen im Alter über 60 Jahre [3][4][5][6][7][8][9]. Die Diagnose wird aufgrund der gezielten Biopsie aus der Kuppe der geröteten hypertrophen Magenfalten im Antrum gesichert: Histologisch wurden schon vor der Einführung des Begriffs "Wassermelonen-Magen" im Biopsiematerial Teleangiektasien, oft mit fokalen Mikrothromben in den dilatierten Kapillaren beschrieben [10,11].…”
Section: Originalarbeit 221unclassified